2017
DOI: 10.1007/s00402-017-2653-7
|View full text |Cite
|
Sign up to set email alerts
|

Fracture reduction by postoperative mobilisation for the treatment of hyperextension injuries of the thoracolumbar spine in patients with ankylosing spinal disorders

Abstract: IntroductionThe aim of this study was to evaluate results of surgical stabilisation of hyperextension injuries of the thoracolumbar spine in patients with ankylosing spinal disorders using two different treatment strategies: the conventional open rigid posterior instrumentation and percutaneous less rigid posterior instrumentation. Surgical and non-surgical complications, the postoperative radiological course, and clinical outcome at final follow-up were comparatively assessed. Moreover, we sought to discuss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…The advent of MISt using PPS in the treatment of vertebral fractures in ankylosing disorders has reduced the morbidity associated with open surgery such as increased blood loss, higher infection rate, longer operative time, higher pain score, longer hospital stay and recovery time 13 , 14 , 25 - 28 . Kruger et al 13 reviewed 10 patients with AS or DISH treated with MISt and reported good mid-term functional outcome with shorter operative time of 60.2 minutes (range, 32-135 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of MISt using PPS in the treatment of vertebral fractures in ankylosing disorders has reduced the morbidity associated with open surgery such as increased blood loss, higher infection rate, longer operative time, higher pain score, longer hospital stay and recovery time 13 , 14 , 25 - 28 . Kruger et al 13 reviewed 10 patients with AS or DISH treated with MISt and reported good mid-term functional outcome with shorter operative time of 60.2 minutes (range, 32-135 min).…”
Section: Discussionmentioning
confidence: 99%
“…Moussallem et al 14 compared 25 patients treated with MISt and 16 patients with open surgery and documented shorter operative time (254.8 vs. 334.7 min, p=0.04), lower blood loss (166.8 vs. 1240.4ml, p<0.001), decreased transfusion rate (36.0% vs. 87.5%, p=0.001), lower complication rate (56.0% vs. 87.0%, p=0.045) and shorter hospital stay (9.6 vs. 16.7 days, p=0.008) in the MISt group. Lindtner et al 28 compared six patients in MISt group and 14 patients in open group and found that the open group had higher post-operative complication rate (1.3 vs. 0.7 complications per patient). Okada et al 29 , in a retrospective review comparing 16 DISH patients undergoing MISt and 25 DISH patients undergoing conventional open surgery for spinal fractures, reported shorter operation duration and lower blood loss in the MISt group.…”
Section: Discussionmentioning
confidence: 99%
“…However, improving reduction of hyperextension spine injuries in ASD patients may be difficult, as the disruption of the anterior column is worsened when the patients are in the prone position. Lindtner et al [ 20 ] described a new treatment concept for the surgical management of hyperextension injuries of the thoracolumbar spine in patients with ASD, involving percutaneous less rigid posterior instrumentation. Fracture reduction by postoperative mobilization is feasible, and seems to facilitate adequate reduction and restoration of the preinjury sagittal alignment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lindtner et al [ 20 ] described a new treatment concept for the surgical management of hyperextension injuries of the thoracolumbar spine in patients with ASD, involving percutaneous less rigid posterior instrumentation. Fracture reduction by postoperative mobilization is feasible, and seems to facilitate adequate reduction and restoration of the preinjury sagittal alignment [ 20 ]. In our study, there were no cases of obvious malalignment, although the disruption of the anterior column did worsen in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Van Royen et al [24,25] have described cases where pseudoarthrosis fixation and fusion was performed along with deformity correction at same level with success; they also described a mathematical formula for such osteotomies. Recently, a series has been published describing postoperative fracture reduction by controlled kyphosis through early mobilization following semi rigid posterior fixation with percutaneous screws [26].…”
Section: Discussionmentioning
confidence: 99%